Transformer engineering : design, technology, and diagnostics - Kulkarni, S. V. (Satish V.); Khaparde, S. A., 1949- (Boca Raton, FL : CRC Press, 2013)
Transformer Engineering: Design, Technology, and Diagnostics, Second Edition helps you design better transformers, apply advanced numerical field computations more effectively, and tackle operational and maintenance issues. Building on the bestselling Transformer Engineering: Design and Practice, this greatly expanded second edition also emphasizes diagnostic aspects and transformer-system interactions.
What's New in This Edition.
Three new chapters on electromagnetic fields in transformers, transformer-system interactions and modeling, and monitoring and diagnostics.
An extensively revised chapter on recent trends in transformer technology.
An extensively updated chapter on short-circuit strength, including failure mechanisms and safety factors.
A step-by-step procedure for designing a transformer.
Updates throughout, reflecting advances in the field.
A blend of theory and practice, this comprehensive book examines aspects of transformer engineering, from design to diagnostics. It thoroughly explains electromagnetic fields and the finite element method to help you solve practical problems related to transformers. Coverage includes important design challenges, such as eddy and stray loss evaluation and control, transient response, short-circuit withstand and strength, and insulation design. The authors also give pointers for further research. Students and engineers starting their careers will appreciate the sample design of a typical power transformer.
Presenting in-depth explanations, modern computational techniques, and emerging trends, this is a valuable reference for those working in the transformer industry, as well as for students and researchers. It offers guidance in optimizing and enhancing transformer design, manufacturing, and condition monitoring to meet the challenges of a highly competitive market. Book jacket.
Includes bibliographical references and index.
Keywords: Electric transformers